Acute acalculous cholecystitis and cardiovascular disease, which came first? After two hundred years still the classic chicken and eggs debate: A review of literature. (June 2022) - Saragò, Martina; Fiore, Davide; De Rosa, Salvatore; Amaddeo, Angela; Pulitanò, Lucrezia; Bozzarello, Cristina; Iannello, Antonio Maria; Sammarco, Giuseppe; Indolfi, Ciro; Rizzuto, Antonia
Abstract: The existence of a close association between disease of the biliary tract and disease of the heart is known from the mists of time. Acute acalculous cholecystitis (AAC) can be defined as an acute necro inflammatory disease of the gallbladder in the absence of cholelithiasis. AAC is a challenging diagnosis. The atypical clinical onset associated to a paucity and similarity of symptoms and to laboratory data mimicking cardiovascular disease (CVD) often results in under and misdiagnosed cases. Moreover, AAC has commonly a fulminant course compared to calculous cholecystitis and it is often associated with gangrene, perforation and empyema as well as considerable morbidity and mortality (up 50%). Early diagnosis is crucial to a prompt treatment in order to avoid complications and to increase survivability. Even today, although scientific evidence dating two hundred years has shown a close association between AAC and CVD, due to the lack of RCT, there is still a lot of confusion regarding the relationship and consequently the clinical management AAC and CVD. In addition, emergency physicians are not always familiar with transient ECG changes with AAC. The aim of this review was to provide evidence regarding epidemiology, pathophysiology, clinical presentation and treatment of the complex association between AAC and CVD. Our main findings indicate that AAC should be suspected after each general disease leading to hypoperfusion such as cardiovascular diseases or cerebrovascular diseases or major heart or aortic surgery. ECG changes in absence of significant laboratory data for IMA (Acute myocardial infarction) could be related to a misdiagnosed AAC. US – Ultrasonography-plays a key role in the early diagnosis and also in the follow up of AAC. Cholecystostomy and cholecystectomy as unique or sequential represent the two prevailing treatment options for AAC. Highlights: AAC should be suspected after each general disease leading to hypoperfusion such as cardiovascular diseases or cerebrovascular diseases or major heart or aortic surgery. ECG changes in absence of significant laboratory data for IMA could be related to a misdiagnosed AAC. Cholecystectomy is an only definitive treatment for AAC. The first report on this theme after 20 years.